PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP PRODUKSI USAHATANI JAGUNG DI DESA BADARAI KECAMATAN WEWIKU KABUPATEN MALAKA - Bano, Anggelita; Suek, Johanna; Nikolaus, Serman; Hendrik, Ernantje (Undana Press, 2023)
This research was conducted in Badarai Village, Wewiku Sub-district, Malacca Regency from January to February 2023. This study aims to (1) estimate corn farming income, and (2) find out what socioeconomic factors affect corn farming production. The results showed that (1) The average revenue earned by hybrid corn farmers is Rp. 11,489,063 with a total production cost of Rp. 2,879,947. Then by using the income formula, the average net income per farmer is Rp. 8,609,116. While the average revenue per hectare is 12,884,930 with a total production cost of Rp. 3,229,847 so that an average net income per hectare of Rp. 9,655,083. (2) Simultaneously, the results show that there is a real influence between age, education level, land area, capital, number of labor, and farming experience on corn farming production. The findings of the partial test indicate that the factors land area, age, capital, number of workers, and farming experience have a substantial impact on corn farming production. Meanwhile, the variable of education level does not significantly affect the production of corn farming in Badarai Village, Wewiku Sub-district, Malaka Regency.